Panduan Praktis Pembuatan Google Bisnisku Sebagai Strategi Digitalisasi UMKM - Stivano Theofilli Kolamban; Filania G. Kapahang; Kristelia Piri; Jesica Rakinaung; Dheanisa Lumain; Grace Christien Sumakul (CV. ITTC INDONESIA, 2025)
Digitalization is an important need for Micro, Small, and Medium Enterprises (MSMEs) in facing increasingly competitive market competition. One of the strategic steps in the digitalization process is the use of the Google My Business platform to increase business visibility in the digital realm. This article aims to provide practical guidance in creating a Google My Business account, strating from the registration process, verification, to optimizing the business profile. Thus, this article is expected to serve as a strategic reference for MSME players who want to strat digital tranformation through simple but effective steps.